Digital Marketing Opportunities for the Advancement of the Tourism Industry Case Study: Indihome PT. Telekomunikasi Indonesia - Sangaji, Abiyyu (Journal of Indonesian Tourism and Policy Studies, 2025)
Digital marketing is becoming increasingly important in the tourism industry as a way to reach a wider target market and increase sales. This study uses a qualitative descriptive method aimed at exploring digital marketing opportunities in the tourism industry through a case study of IndiHome PT. Telekomunikasi Indonesia. The results of the study indicate that digital marketing can provide significant opportunities for the tourism industry, particularly in terms of the use of social media, websites, and engaging visual content. Furthermore, the results also show that the use of data and analytics can help companies optimize their digital marketing campaigns. However, challenges such as intense competition and changing consumer trends also need to be considered in implementing digital marketing strategies. Thus, this study provides important insights for the tourism industry, especially for companies seeking to expand their market reach through digital marketing.